Total atrial conduction time and its relationship with morphological & functional characteristics in hypertrophic cardiomyopathy. (4th February 2022) - Pagourelias, E; Boulmpou, A; Alexandridis, G; Tsarouchas, A; Mouselimis, D; Bakogiannis, K; Karamanolis, A; Vergopoulos, S; Tsavousoglou, C; Antoniadis, A; Fragakis, N; Papadopoulos, CE; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Total atrial conduction time (TACT), estimated by tissue Doppler imaging (TDI), is an index reflecting left atrial (LA) structural and electrical remodeling, connected to atrial fibrillation (AF) development and heart failure progression in various substrates. In hypertrophic cardiomyopathy (HCM), the significance of TACT beyond AF and its determinants are not fully investigated. Purpose: Aim of this study was to estimate TACT in a cohort of HCM patients without AF history and to examine its relationship with other parameters of atrial myopathy, such as LA volume index (LAVI) or LA reservoir strain (LARS). Additionally, to investigate TACT correlation with other phenotypic and functional characteristics of HCM. Methods:  We included 50 HCM patients (60 ± 16 years, 80% male, maximum wall thickness 18.6 ± 4.1mm) without history of AF who have consecutively undergone 2D-speckle tracking echocardiography and cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE). TACT was measured from the onset P wave on electrocardiogram to the peak A' wave of the lateral LA wall using TDI (left panel). Burden of fibrosis (percentage of LV mass) was defined by LGE extent (>5 standard deviations compared to nulled myocardium) in CMR slices. Cut-off points for TACT, LAVI and LARS were adopted by literature (≥115 msec, ≥34 mL/m2 and <21.3 % respectively). Results:  All HCM patients had preserved EF (61.8 ± 8%), while 13 (26%) presented outflow tract obstruction and 4 (8%) diastolic dysfunction stage≥2. LGE was observed in 32 patients (64%) occupying 7.2 ± 5% of left ventricular (LV) mass. Mean TACT was 139.9 ± 22 msec, with LAVI being 30.8 ± 16.1 mL/m2 and LARS 27.6 ± 13.9%. After assessing prevalence of atrial myopathy parameters, 41 patients (82%) presented a prolonged (≥115 msec) TACT with only 13 of them having also a significantly dilated LA (≥34 mL/m2) and 16 an impaired LARS. Among HCM demographic, phenotypic and functional characteristics tested, age and LV mass index were found to be the only independent regressors of TACT (r = 0.54, p < 0.0005 and r = 0.44, p = 0.002 respectively, right panels). On the contrary, no significant correlation was established between TACT and traditional diastolic dysfunction indices such as E/E' or fibrosis extent. Conclusions: Atrial electro-mechanical delay assessed through TDI based TACT, is very frequent among HCM patients irrespective of AF and even before LA dilatation and LA strain impairment.  Age and hypertrophy magnitude are the main determinants of TACT, the prognostic significance of which remains to be further elucidated.